Oxidative Precipitation of Manganese from Acid Mine Drainage by Potassium Permanganate - Regeane M. Freitas; Thomaz A. G. Perilli; Ana Claudia Q. Ladeira (Journal of Chemistry)
Although oxidative precipitation by potassium permanganate is a widely recognised process for manganese removal, research dealing with highly contaminated acid mine drainage (AMD) has yet to be performed. The present study investigated the efficiency of KMnO4 in removing manganese from AMD effluents. Samples of AMD that originated from inactive uranium mine in Brazil were chemically characterised and treated by KMnO4 at pH 3.0, 5.0, and 7.0. Analyses by Raman spectroscopy and geochemical modelling using PHREEQC code were employed to assess solid phases. Results indicated that the manganese was rapidly oxidised by KMnO4 in a process enhanced at higher pH. The greatest removal, that is, 99%, occurred at pH 7.0, when treated waters presented manganese levels as low as 1.0 mg/L, the limit established by the Brazilian legislation. Birnessite (MnO2), hausmannite (Mn3O4), and manganite (MnOOH) were detected by Raman spectroscopy. These phases were consistently identified by the geochemical model, which also predicted phases containing iron, uranium, manganese, and aluminium during the correction of the pH as well as bixbyite (Mn2O3), nsutite (MnO2), pyrolusite (MnO2), and fluorite (CaF2) following the KMnO4 addition.